Management accounting practices in Malaysia: a qualitative enquiry - Annuar, Hairul Azlan; Salihu, Ibrahim Aramide (2014)
The conventional wisdom of the obsoleteness of traditional management accounting tools and appropriateness of the contemporary ones has not been empirically established. Several studies have been conducted to ascertain the reasons for such unexpected findings. However, these studies are majorly survey based approaches and there are calls for more rigorous qualitative investigations. This study answers these calls by qualitatively investigating the management accounting practices of ten companies listed on Bursa Malaysia. These companies comprised of foreign and local ones, and also large and small ones. The use of both tools was documented in all the sampled companies. One major reason for this, unveiled in this study, is non-suitability of most of contemporary tools given the environment where they developed. It was recommended that the contemporary tools be implemented using cautious steps of adaptation rather that direct adoption.